Rancang Bangun Sistem Informasi Monitoring Pengadaan Berbasis Web untuk Meningkatkan Transparansi dan Efisiensi Verifikasi Dokumen: Studi Kasus Dinas Komunikasi dan Informatika Kota Surabaya - Dianggi Noor Ayu Astari Putri; Made Kamisutara (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
Dinas Komunikasi dan Informatika, in supporting the achievement of the city’s development targets, carries out the good result procurement and services through the preparation of procurement documents by each division and the verification of payment documents by Sub Bagian Keuangan. However, the verification process still many challenges, including inconsistencies between documents, incomplete documentation according to regulations, delays in document revision, and the risk of document loss due to non-integrated document management. In addition, the lack of real-time monitoring and coordination among divisions, Sub Bagian Keuangan, and vendors or providers causes the verification process slowly and not efficient. Target this study to develop management information system with web-based for monitoring procurement activities that control and tracking of procurement status, so improve the effectiveness, transparency, and accountability of procurement management. This system used Waterfall method, including problem identification, requirements analysis, system design, and evaluation stages. The system is developed as a web-based application developed using the PHP programming language with MySQL as the database management system. The result of this study is a web-based procurement monitoring system application implemented at Sub Bagian Keuangan of Dinas Komunikasi dan Informatika. System evaluation through black-box testing shows that all five core functional scenarios passed as expected (5/5 valid).